Peran Kinerja Keuangan Dalam Memediasi Corporate Governance Pada Corporate Internet Reporting - Rahmawati, Alifia Nur; Susilowati, Endah (Universitas Gorontalo, 2023)
This research was done to see if financial performance could act as a mediating factor between corporate governance's influence and corporate online reporting. 58 companies were selected as examples using secondary data from company disclosures on the IDX80 recorded companies' website in 2022. The technique of route analysis method and SEM-PLS method-based hypothesis testing tools are used in the analytical process. The study's findings demonstrate that corporate governance has no impact on financial performance. Another indicates that both company governance and financial performance have an effect on corporate internet reporting in a negative way and corporate governance has an impact on corporate internet reporting. The influence of corporate governance on corporate internet reporting, which is a recent development in this study, cannot be mediated by financial performance.